P‐34: Automotive Local dimming Integrated System for LCD MDL. Issue 1 (28th June 2022) - Wang, Xiaoxia; Dong, Xiaoqiao; Yu, Jie; Han, Rui; Ma, Qing; Cui, Dong; Yoon, D.K.; Zhang, Yicai; Cai, Site; Qiao, Xuanxuan
Abstract : BOE has developed a 12.3‐inch on‐board display module that integrated local dimming driving system and algorithm. It can achieve high image quality, ultra‐high contrast and low power consumption under the vehicle UI interface. Meanwhile, it has passed the reliability test of vehicle LCD module, and can be applied directly to vehicle display to provide users safer and better driving experiences.